Ritual performance in early Chinese thought: a dramaturgical perspective - Radice, Thomas (Bloomsbury Academic, 2025)
"This book analyzes early Chinese ritual discourse during the Warring States and early Western Han Periods, arguing that the Ruists (Confucians) conceived ritual as primarily a dramaturgical matter, which had wide-ranging effects on the ways authors of early Chinese texts discussed matters of religion, ethics, and politics. It reveals how performance became a fundamental feature of political life, making theatrical "presence" a necessary element for either expression or deception in a community of spectators"--